An overview of Mycotoxin contamination of animal feeds - Hassan, MZ; Rahman, MM; Ali, MZ; Yousuf, MA; Akther, S; Rahman, MH; Islam, MA; Hossen, A (Bangladesh Journal of Livestock Research, 2020)
Mycotoxins contamination of animal feeds remains a great concern for animal feed safety, public health and economic significance. It may occur in various foods and feeds stuffs from agricultural commodities to finished foods and feeds of animal. Hot, humid weather and late harvesting of grains favored the mold and fungal growth in cereal crops. There are around 400 types of mycotoxins in which aflatoxin, deoxyinalenol (vomitoxin), fumonisin, zearalenone and ochratoxins are important for animal and human foods. However, presence of mold or fungi in the grains does not mean that mycotoxins are present in feeds or foods. The acceptable level of aflatoxins, deoxyinalenol (vomitoxin), fumonisin, zearalenone and ochratoxins are in livestock feeds are 20 ppb, 10 ppm, 5 ppm and 3-10 ppm and 3-20 (μg/kg) respectively. Mycotoxins can be found in contaminated cereal grains, straw and silage. The most detrimental effects of mycotoxins are hepatic, digestive, immunological, reproductive disorders, teratogenicity, nephrotoxicity, edema and carcinogenicity etc. of animal and human being. Adsorbents and activated charcoal in animal feeds bind the toxic substances. There are some regulations but not in all countries aimed to prevent and control mycotoxins in industrial processed foods and animal feeds but not in locally processed ones. A number of strategies in some countries for preventing mycotoxins have been mobilized but the awareness for implementation is very weak. Mass media can play an important role to build awareness to mycotoxin. Bangladesh J. of Livestock Res. 21-25: 1-9, 2018